ANALISIS INTERNATIONAL FINANCIAL REPORTING STANDART (IFRS) PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agnes Susana Merry Purwati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
Accounting information is basically help ful to take adecision-making within the company.one of theforms ofaccounting informationis the financial statement. Therefore, accounting informationmust bequalified. This study aimstoanalyze the differences inthe quality of accounting informationbetween before and after the adoption of International Financial Reporting Standards (IFRS) into theIa Sonautomotive companies listed in Indonesia Stock Exchange.The results showed thatearnings management decreasedantatra before and after theadoption ofI FRS. But seen from the results ofpaired sample sttest wheresig (2 failed) for0.937>0.05, it can be concluded that Ho is accepted which means there is no difference in thequality of accounting information before and after the adoption ofI FRS